Online Learning Motivation of Senior High School Students and How It Relates to Their Online Learning Participation Rate - Sinadia, Alfrits Roul; Sondakh, Prilia Mawarni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2023)
Abstract: This study was conducted due to the low level of online learning participation observed during the second year of online learning implementation due to the COVID-19 pandemic in Indonesia. It aimed to discover the relationship between online learning motivation level and online learning participation rate. It also sought to study the difference between males and females in terms of online learning motivation levels. It was a descriptive, differential, and correlational quantitative study using the survey method. The population of this study was Grade XI students of a private senior high school. The students took part in filling out a paper-based questionnaire and the data were analyzed using descriptive and inferential statistics. The analysis results showed that there was a significant correlation between students’ online learning motivation level and their online learning participation rate. Another important result was that there was a significant difference between males and females in terms of online learning motivation levels. It was concluded that the higher students’ level of online motivation, the higher their online learning participation rate would be. Finally, males have a slightly higher online motivation level than females. Keywords: motivation, online learning, learning motivation, learning participation, online learning motivation, the online learning participation rate